-3(-4y+u)-5(-6u-6y)=

Simple and best practice solution for -3(-4y+u)-5(-6u-6y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-4y+u)-5(-6u-6y)= equation:


Simplifying
-3(-4y + u) + -5(-6u + -6y) = 0

Reorder the terms:
-3(u + -4y) + -5(-6u + -6y) = 0
(u * -3 + -4y * -3) + -5(-6u + -6y) = 0
(-3u + 12y) + -5(-6u + -6y) = 0
-3u + 12y + (-6u * -5 + -6y * -5) = 0
-3u + 12y + (30u + 30y) = 0

Reorder the terms:
-3u + 30u + 12y + 30y = 0

Combine like terms: -3u + 30u = 27u
27u + 12y + 30y = 0

Combine like terms: 12y + 30y = 42y
27u + 42y = 0

Solving
27u + 42y = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-42y' to each side of the equation.
27u + 42y + -42y = 0 + -42y

Combine like terms: 42y + -42y = 0
27u + 0 = 0 + -42y
27u = 0 + -42y
Remove the zero:
27u = -42y

Divide each side by '27'.
u = -1.555555556y

Simplifying
u = -1.555555556y

See similar equations:

| 1.8b=0.9 | | 8(2)=3(x+3) | | 8(x-3)=6x+11-5x | | 42+22x=180 | | 13x+9x-8+50=180 | | 5x+90=2x-15 | | (32x-7y)-(28x-11y)=0 | | 1.6h+72=4h-30 | | -30x^2+35x-10=0 | | -4.42x+.9=-9.070-0.432 | | 11x-10y=30 | | 60+.50(200)=1.30(200) | | 20x-9(3)=7 | | 19+[3x(7-3)]-2= | | .5(-4x-5)=7x-.5 | | 3x^3-3x^6-9x^3+5=0 | | 65-85=x | | (x-1)(2x)(x-4)=40 | | 5d-33=7.2 | | 32x=5x-14 | | r/3-4=3 | | 3x-(2x-1)=5x+1-4x | | 60+.50(100)=1.30(100) | | -5.26+.21x=19.94 | | 7cos(7x)=0 | | 16x^2-4x+5-(16x^2-8x)+1=0 | | -12x-11=-47 | | 7(-8x)= | | -4x=12-x^2 | | -z-9=3.4(2z+4.3) | | -5.26+.21x=15.74 | | 20x-16y=48 |

Equations solver categories